2020
DOI: 10.1021/acs.jafc.0c02815
|View full text |Cite
|
Sign up to set email alerts
|

Wheat (Triticum aestivum L.) Breeding from 1891 to 2010 Contributed to Increasing Yield and Glutenin Contents but Decreasing Protein and Gliadin Contents

Abstract: Epidemiologic studies suggest an increasing prevalence of celiac disease and non-celiac gluten/wheat sensitivity. With wheat proteins being the main triggers, changes in wheat protein composition are discussed as a potential cause. The goals of breeding toward increased yield and resistance might have inadvertently contributed to a higher immunostimulatory potential of modern wheat cultivars compared to old wheat cultivars. Therefore, agronomic characteristics, protein content, and gluten composition of 60 Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 49 publications
8
54
0
1
Order By: Relevance
“…All studies report a substantial influence of the growing conditions on the content and composition of wheat proteins. Regarding protein composition, an increase in glutenins and a decrease in gliadins and gliadin/glutenin ratios, but essentially no changes for albumins/globulins and gluten, were observed in German winter wheat cultivars from 1891 to 2010, all grown at the same location in three consecutive years (189). Similar results were reported by Ozuna and Barro (190).…”
Section: The Increasing Prevalence Of Wheat-related Disorderssupporting
confidence: 84%
“…All studies report a substantial influence of the growing conditions on the content and composition of wheat proteins. Regarding protein composition, an increase in glutenins and a decrease in gliadins and gliadin/glutenin ratios, but essentially no changes for albumins/globulins and gluten, were observed in German winter wheat cultivars from 1891 to 2010, all grown at the same location in three consecutive years (189). Similar results were reported by Ozuna and Barro (190).…”
Section: The Increasing Prevalence Of Wheat-related Disorderssupporting
confidence: 84%
“…PCA, principal component analysis [Colour figure can be viewed at wileyonlinelibrary.com] extractable proteins. At first glance, it becomes obvious that the harvest year had a strong influence on the cluster formation and distribution of the cultivars ( Figure S4), which is in accordance with our previous study (Pronin et al, 2020) and also evident using the traditional integration method. One reason for the stronger clustering of the wheat cultivars might be that this year had the least amount of annual mean precipitation (366 mm, as opposed to 533 mm and 557 mm in 2015 and 2017, respectively), but further investigations would be necessary to establish a clear cause-effect relation here.…”
Section: Distinction Of Wheat Cultivars Using the New Integration Msupporting
confidence: 89%
“…The observations made for the average over three harvest years were influenced by the harvest year 2016 ( Figure S4b), since the clusters for the harvest years 2015 and 2017 were mostly overlapping and therefore difficult to distinguish. These observations are consistent with the fact the harvest year had a significant effect on the protein distribution of the 60 wheat cultivars (Pronin et al, 2020). Effectively, there is a lack of studies performing a comprehensive comparison of wheat protein patterns by means of RP-HPLC, except for the study by Daniel and Triboi (2000) that revealed significant differences between the gliadin chromatograms of a winter wheat cultivar influenced by the effects of temperature and fertilization.…”
Section: Distinction Of Wheat Cultivars Using the New Integration Msupporting
confidence: 71%
See 2 more Smart Citations